A Preliminary Assessment of Gut Helminths of Two Synanthropic Foragers, Cattle Egret (Bubulcus ibis), and the African Pied Crow (Corvus albus), on a University Campus, Ghana - Bimi, Langbong; Anto, Francis; Hanson, Tracy; Okofo-Mensah, Mariam; Sawyerr, Louisa Modukpe; Tetteh, Ato Kwamena (The Asia Journal of Applied Microbiology, 2020)
Objective: This study was carried out in Legon, Accra to determine the occurrence of parasitic helminths infecting the cattle egret and the African pied crow. Methods: Between January and April of 2019, the two bird species were trapped, and their gastrointestinal contents and droppings examined for adult parasites and ova. Results: Identified GIT parasites included adult worms (adult tapeworm and adult Strongyloides sp) and ova (hookworm, Trichuris, Trichostrongylus, Strongyloides, Paragonimus, and Diphyllobothrium species). With regards to GIT examination, 38 Trichuris species ova (mostly in the gizzard) and five (5) adult tape worms (in the ileum and colon) were detected in the African pied crows. In the cattle egret, four (4) Trichuris sp ova, three (3) hookworm ova and one (1) adult Strongyloides sp were detected in the ileum and colon only. Forty-one (41) ova (six of the types above) were detected in the 45 cattle egret droppings processed. Trichuris sp (31.7%, 13/41) and hookworm (26.8%, 11/41) constituted the majority. Conclusion: Overall, helminth richness was found to be higher in the cattle egret compared to the African pied crow. The outcome of this study provides preliminary information on helminth types in these two birds, and has negative public health implications.